Optimize contract law - Hough, Tracey; Kuhnel-Fitchen, Kathrin (Milton Park, Abingdon, Oxon : Routledge, 2014)
'The Optimize series is designed to show you how to apply your knowledge in assessment. These concise revision guides cover the most commonly taught topics, and provide you with the tools to: Understand the law and remember the detailsusing diagrams and tables throughout to demonstrate how the law fits togetherContextualise your knowledgeidentifying and explaining how to apply legal principles for important casesproviding cross-references and further reading to help you aim higher in essays and examsAvoid common misunderstandings and errorsidentifying common pitfalls students encounter in class and in assessment Reflect critically on the lawidentifying contentious areas that are up for debate and on which you will need to form an opinionApply what you have learned in assessmentpresenting learning objectives that reflect typical assessment criteriaproviding sample essay and exam questions, supported by end-of chapter feedback The series is also supported by comprehensive online resources that allow you to test your progress during the run-up to exams'--
'The Optimize series is designed to show you how to apply your knowledge in assessment. These concise revision guides cover the most commonly taught topics, and provide you with the tools to: Understand the law and remember the details Contextualise your knowledge Avoid common misunderstandings and errors Reflect critically on the law Apply what you have learned in assessment'--
Offer and acceptance -- Consideration -- Terms -- Misrepresentation -- Mistake -- Duress and undue influence -- Illegal contracts and contracts in restraint of trade -- Discharge of contract -- Remedies.
Includes index.
Keywords: Contracts -- United Kingdom